2002
DOI: 10.1038/415810a
|View full text |Cite
|
Sign up to set email alerts
|

The non-coding Air RNA is required for silencing autosomal imprinted genes

Abstract: In genomic imprinting, one of the two parental alleles of an autosomal gene is silenced epigenetically by a cis-acting mechanism. A bidirectional silencer for a 400-kilobase region that contains three imprinted, maternally expressed protein-coding genes (Igf2r/Slc22a2/Slc22a3) has been shown by targeted deletion to be located in a sequence of 3.7 kilobases, which also contains the promoter for the imprinted, paternally expressed non-coding Air RNA. Expression of Air is correlated with repression of all three g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

19
779
1
7

Year Published

2003
2003
2007
2007

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 973 publications
(818 citation statements)
references
References 24 publications
19
779
1
7
Order By: Relevance
“…When both transcriptional units are active, formation of dsRNA occurs by default, leading to histone modification and TGS: SATs effectively cancel each other, relaxing the need for stringent regulation of promoter engagement by transcription factors. An example is the imprinting of the gene Igf2r in mice 50 . Expression of Igfr2 depends on whether the locus is inherited from either the mother or the father.…”
Section: Rna-directed Dna Read-outmentioning
confidence: 99%
See 1 more Smart Citation
“…When both transcriptional units are active, formation of dsRNA occurs by default, leading to histone modification and TGS: SATs effectively cancel each other, relaxing the need for stringent regulation of promoter engagement by transcription factors. An example is the imprinting of the gene Igf2r in mice 50 . Expression of Igfr2 depends on whether the locus is inherited from either the mother or the father.…”
Section: Rna-directed Dna Read-outmentioning
confidence: 99%
“…Expression from the paternal chromosome is prevented by an antisense transcript produced by the non-protein coding gene Air. Net expression of Igfr2 occurs only from the maternal chromosome, as methylation of the maternal Air gene promoter prevents production of an antisense transcript 50 . This mechanism might be quite general.…”
Section: Rna-directed Dna Read-outmentioning
confidence: 99%
“…On the maternal chromosome, DNA methylation prevents transcription of Air and Kcnq1ot1, allowing clusters of imprinted genes to be expressed (Stoger et al, 1993;Engemann et al, 2000). On the paternal chromosome, all three coding genes in the Igf2r cluster, Igf2r, slc22a2, and slc22a3, are silenced by Air, even though it is only antisense to Igf2r (Sleutels et al, 2002). How Air silences Igf2r cluster remains to be determined, but regulatory mechanisms behind the silencing of Kcnq1 may yield some clues.…”
Section: Genomic Imprintingmentioning
confidence: 99%
“…(2) Noncoding RNAs act in cis to regulate gene expression. Sleutels et al [2002] showed that, in the mouse Igf2r imprinted cluster, truncation of the noncoding Air RNA that is transcribed from its promoter in the IC causes loss of imprinting for all genes in the cluster. However, in the PWS/AS region, a deletion extending from Snrpn intron 1 to Ube3a intron 1 removes almost all of the paternally-expressed region downstream from the PWS-IC, but paternal deletion of this region has no effect on imprinted expression of Ndn [Tsai et al, 1999].…”
Section: Summary Synthesis and Extension To Other Imprinted Regionsmentioning
confidence: 99%